Treatment of seborrheic keratosis in bilateral external auditory canal using fiber CO2 laser - Cevizci, Raşit; Üstün Bezgin, Selin; Altın, Gökhan; Oran, Gülbin; Bayazıt, Yıldırım Ahmet (My University, 2016)
In this article, we report a 33-year-old female patient with lesions of bilateral external auditory canals who was treated using fiber CO2 laser without canaloplasty. Histopathological examination confirmed the diagnosis of irritated type seborrheic keratosis, which is rare in external auditory canal. Twelve months after the treatment, the patient showed no signs of recurrence.

Bu makalede, iki taraflı dış kulak kanallarında lezyonlar olan ve kanaloplasti olmadan fiber CO2 lazer kullanılarak tedavi edilen 33 yaşında bir kadın hasta sunuldu. Dış kulak kanalında nadir görülen irrite tip seboreik keratoz tanısı histopatolojik incelemede doğrulandı. Tedaviden 12 ay sonra hastada herhangi bir nüks belirtisi görülmedi.
Fiber CO2 lazer kullanarak iki taraflı dış kulak kanalında seboreik keratoz tedavisi
Keywords: External Auditory Canal; Laser; Seborrheic Keratosis; Dış Kulak Kanalı; Lazer; Seboreik Keratoz